SEMANTIC AND PRAGMATIC CHARACTERISTICS OF SOMATIC PHRASEOLOGICAL UNITS IN UZBEK AND ENGLISH - Allanazarova, Feruza Karimberdievna; Tursinbaeva, Aygul Rajabovna (SCIENCE and SOCIETY, 2026)
The article examines the semantic and pragmatic features of somatic phraseological units (SPU) in the Uzbek and English languages.SPUs are idiomatic expressions that involve human body parts and convey figurative meanings beyond their literal sense.